THE EFFORTS OF ISLAMIC RELIGIOUS EDUCATION (PAI) TEACHERS IN ACTUALIZING PROFESSIONAL ETHICS THROUGH EFFECTIVE COMMUNICATION WITH STUDENTS AT SDN LARANGAN LUAR 2 - Amelia Diviana Putri; Desy Nur Hayati; Sholehatus Sakdiyah; Rofiq Hidayatullah; Abd. Mukhid (SOSIOEDUKASI, 2026)
This research aims to examine the strategies of Islamic Religious Education (PAI) teachers in actualizing professional ethics through effective communication with students at SDN Larangan Luar 2. This research emphasizes that Islamic Religious Education (PAI) educators serve as ethical exemplars and spiritual mentors, becoming skilled communication vital to their professional principles. Employing a qualitative descriptive methodology depending on interviews, observations, and document analysis with principals, educators, and students the study indicates that these educators employ a variety of essential communication techniques. This encompasses straightforward, gentle spoken By weaving religious communication into daily lessons, PAI teachers effectively foster a positive classroom atmosphere, boost student engagement, and cultivate disciplined, respectful behavior. However, there are obstacles such as diverse student characteristics and limited lesson duration. These results conclude that effective communication plays a central role in realizing the professional ethics of Islamic Religious Education (PAI) teachers. Therefore, teachers need to continuously develop communication skills to optimally fulfill their professional duties in shaping students' character.